Post-treatment with an inhibitor of poly(ADP-ribose) polymerase attenuates cerebral damage in focal ischemia - Kazushi Takahashi; Andrew A. Pieper; Sidney Croul; Jie Zhang; Solomon H. Snyder; Joel Greenberg (1999)
Poly(ADP-ribose) polymerase (PARP) is thought to play a physiological role in maintaining genomic integrity and in the repair of DNA strand breaks. However, the activation of PARP by free radical-damaged DNA plays a pivotal role in mediating ischemia–reperfusion injury. The excessive activation of PARP causes a rapid depletion of intracellular energy leading to cell death. The present study examined the effect of post-ischemic pharmacological inhibition of PARP in a rat focal cerebral ischemia model. In Long–Evans rats, focal cerebral ischemia was produced by cauterization of the right distal middle cerebral artery (MCA) with bilateral temporary common carotid artery (CCA) occlusion for 90 min. A PARP inhibitor, 3,4-dihydro-5-[4-(1-piperidinyl)butoxy]-1(2H)-isoquinolinone (DPQ; IC50=1 μM/l) was injected i.p. 30 min after the onset of MCA occlusion (control: 10, 20, 40 and 80 mg/kg; n=7 each). Twenty-four hours later, the total infarct volume was measured. Regional blood flow in the right parietal cortex decreased to approximately 20% of the baseline following MCA occlusion in all groups. PARP inhibition lead to a significant decrease in damaged volume in all treated groups with the largest reduction in the 40 mg/kg group (111.5±24.8 mm3, mean±SD, p<0.01), compared to the control group (193.5±28.6 mm3). We also found there was a significant increase of poly(ADP-ribose) immunoreactivity in the ischemic region, as compared to the contralateral side, with DPQ treatment diminishing poly(ADP-ribose) production. These findings indicate that DPQ exerts its neuroprotective effects in vivo by PARP inhibition and that PARP inhibitors may be effective for treating ischemic stroke, even when the treatment is initiated after the onset of ischemia.